PERTIMBANGAN HAKIM MEMBERIKAN HAK ASUH ANAK KEPADA AYAH: SUATU KAJIAN EMPIRIS DI MAHKAMAH SYAR’IYAH BANDA ACEH - Mansari, Mansari (Petita : Jurnal Kajian Ilmu Hukum dan Syariah, 2016)
In fact the justices not always give the foster rights for mother. In some cases there are several judgement that justices deliver foster rights for father, stated in judgement Number putusan Nomor 65/Pdt.G/2011/MS-Bna, 167/Pdt.G/2011/MS–Bna dan 66/Pdt.G/2012/MS-Bna. Justices has carefully delivered foster rights in some cases. The main consideration is fulfilling the best interest of child. Thus justices must carefully a social condition of carer candidate. Islamic law gives priority to a person who has responsibility and can fulfil his job as carer (hadhin). Even though a mother has legal rights to foster his children, but if she does not have ability in term of social economic, she can deliver his rights to the child’s father. Justices suggested in giving foster rights must consider psychological aspects between child and his career, to ensure the carer candidate have strong responsibility in fostering child under his guardianship.